2018
DOI: 10.1039/c8ta06470a
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculations and experimental studies of XYZ2 thermoelectric compounds: detailed analysis of van der Waals interactions

Abstract: van der Waals interactions enhanced the prediction of properties in layered thermoelectrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 82 publications
(131 reference statements)
2
10
0
Order By: Relevance
“…On the other hand, hybrid functionals do not affect the curvature of band edges but widen the band gap, as seen in Figure S12 (Supporting Information). In agreement with our findings, previous studies have shown that hybrid-DFT calculations are not superior to the DFT for the calculation of transport properties in TE materials. …”
Section: Methodssupporting
confidence: 92%
“…On the other hand, hybrid functionals do not affect the curvature of band edges but widen the band gap, as seen in Figure S12 (Supporting Information). In agreement with our findings, previous studies have shown that hybrid-DFT calculations are not superior to the DFT for the calculation of transport properties in TE materials. …”
Section: Methodssupporting
confidence: 92%
“…Among those, CuTmTe 2 , AgTmTe 2 , and AgBiSe 2 are experimentally established good thermoelectric materials. First-principles calculations also predicted other related “112” (such as YAgTe 2 , YCuTe 2 ) compounds as promising thermoelectric materials …”
Section: Introductionmentioning
confidence: 83%
“…The Pauli paramagnetism, low Seebeck coefficient, and high thermal conductivity indicate that CuNiSb 2 is not a potential magnetic or thermoelectric material. However, CuNiSb 2 represents a rare case of “112” in ternary pnictides and provides a reference for further study of “112” compounds of which many are predicted to be promising thermoelectrics . More “112” ternary pnictides such as T 1 T 2 Pn 2 or RTPn 2 (T = transition metal, R = rare-earth metal) with metal-ordered NiAs-derived structure require further exploration using solid-state methods at ambient and high pressure and/or other synthetic methods including Sb, Bi, and salt fluxes.…”
Section: Discussionmentioning
confidence: 99%
“…Motivated by the search for new efficient renewable sources of energy, a huge experimental effort has been made towards identifying materials with better thermoelectric properties in the recent years. So far, this intense search has been based mostly on a single particle theoretical description of electrons and standard electron-phonon coupling due to displacement potential, supported by numerical ab-initio simulations [1] [2]. While this research program has had some notable successes [3] it should be also noted that the progress has been slow and so novel pathways are needed.…”
Section: Pacs Numbersmentioning
confidence: 99%